A Combined Experimental and Molecular Dynamics Simulation Study on the Miscibility of Eucommia Ulmoides Gum with Several Rubbers. Issue 1 (January 2017) - Li, Fei-Zhou; Lu, Zhen-Lin; Tian, Dong-Ping
This paper analyzes the miscibility state of EUG blended with CR, BR, SBR, NR and NBR via Molecular Dynamics (MD) simulations performed using Blends and the Flory-Huggins interaction parameter, phase diagrams, and mixing energy. The results showed that EUG can be miscible with CR, BR, SBR, NR, and NBR above 350K, and the simulation predictions and experimental results were mainly the same.